Evaluation problemorientierter integrativer Umweltforschung: Hintergründe, Probleme und Ansätze - Manstetten, Reiner; Schiller, Johannes; Klauer, Bernd; Steuer, Philipp; Unnerstall, Herwig; Wittmer, Heidi; Hansjürgens, Bernd (UFZ-Diskussionspapiere, 2005)
Governance has definitely become a very iridescent concept in recent years. The term is widely used, meanwhile, in almost all social-science disciplines as well as in the political process. The intention of this paper is not so much to clarify these sometimes vague meanings but to highlight some special characteristics of environmental governance connected with the restructuring of the spatial dimensions of politics. It starts from the assumption that the quest for multi-level decision making is particularly pressing for environmental governance. However, multi-level governance raises concern about the constitution of various spatial levels and their relationships with each other, as discussed under the term of 'politics of scale'. Moreover, it is argued that for environmental governance the spatial reference is strongly connected with another challenge, which concerns the question of how to deal with the biophysical conditions of particular places? The term landscape governance is introduced to tackle this question without referring to an ontologically given space. Thus, landscape governance deals with the interconnections between socially constructed spaces (the politics of scale) and 'natural' conditions of places. For this task, the concept of societal relationships with nature is introduced and applied to the term 'landscape' as a bridging concept between social and natural sciences. The paper illustrates the approach of landscape governance with examples of problem-oriented interdisciplinary research at the UFZ-Centre for Environmental research in Leipzig, eastern Germany.
Parallel als Druckausg. erschienen
Keywords: Arbeitspapier; Graue Literatur